Analisis Pesan Dakwah Yang Terkandung Dalam Sinetron Pera Pencari Tuhan Jilid 14 - Ariefuddin Qhamarullah; Asep Gunawan; Noneng Siti Rosidah (KOLONI, 2023)
Sinetron (Indonesian Soap opera) are a medium that functions to convey messages in audio-visual form. As an information medium, sinetron (Indonesian soap operas) can be said to be the most effective medium in conveying messages containing da'wah to the public. One of the Sinetron (Indonesian Soap opera) that can convey messages containing da'wah is the sinetron (Indonesian soap opera) "Para Pencari God Volume 14" which not only provides education but also preaching messages to its viewers. The interesting thing about this sinetron (Indonesian Soap opera) is that it dares to raise issues that are considered current, such as current conditions. Therefore, the author is interested in researching a s Sinetron (Indonesian Soap opera) entitled "Para Pencari tuhan jilid 14" by Citra Cinema regarding the preaching message contained in each scene, then interpreted using Ferdinand De Sausssure's semiotic analysis method. Based on the background above, the research question posed by the author is: what is the meaning of the preaching message of commendable morals towards fellow humans in the semiotic analysis of Ferdinand De Saussure in the Sinetron (Indonesian Soap opera) Para Pencari tuhan jilid 14. The aim of this research is: to find out the meaning of the preaching message contained in the Sinetron (Indonesian Soap opera) "Para Pencari tuhan jilid 14" uses Ferdinand De Saussure's semiotic analysis. This research was conducted using qualitative research with a semiotic analysis approach. The data sources used in this research are primary data, namely the video of the Sinetron (Indonesian Soap opera) “Para Pencari tuhan jilid 14” which was uploaded on YouTube and secondary data in the form of photos, documents, articles, journals and books. Data collection techniques were carried out using non-participant observation and documentation. The data analysis technique used is Ferdinand De Saussure's semiotic model which interprets the meaning of signifier (signifier) and signified (signified). Based on the results of the analysis and discussion, the author concludes that the meaning of the da'wah message contained in the Sinetron (Indonesian Soap opera) “Para pencari tuhan jilid 14” in Ferdinand De Saussure's analysis is 1) giving help, 2) giving advice, 3) saying and answering greetings, 4) saying the truth, 5 ) keeping the mandate, 6) keeping one's gaze, 7) inviting good things, 8) forgiving and forgiving each other, 9) smiling when they meet, and 10) holding back anger.